Safety and immunogenicity of double-dose versus standard-dose hepatitis B revaccination in non-responding adults with HIV-1 (ANRS HB04 B-BOOST): a multicentre, open-label, randomised controlled trial. Issue 11 (November 2015) - Rey, David; Piroth, Lionel; Wendling, Marie-Josée; Miailhes, Patrick; Michel, Marie-Louise; Dufour, Cécilie; Haour, Georges; Sogni, Philippe; Rohel, Alexandra; Ajana, Faiza; Billaud, Eric; Molina, Jean-Michel; et al.
Summary: Background: Revaccination with double-dose hepatitis B vaccine has been recommended in HIV-infected patients who do not respond to standard vaccination, but has not yet been assessed. We aimed to compare the safety and immunogenicity of a reinforced hepatitis B revaccination protocol with the standard revaccination schedule in HIV-infected patients not responding to primary vaccination. Methods: We did this multicentre, open-label, randomised controlled trial, at 53 centres in France. HIV-infected adults (aged ≥18 years), with CD4 counts of 200 cells per μL or more and no response to a previous hepatitis B vaccination or a 20 μg booster dose, were randomly assigned (1:1), according to a computer-generated randomisation list with permuted blocks (block sizes of two to six), to receive either standard-dose (20 μg) or double-dose (40 μg) recombinant hepatitis B vaccine at weeks 0, 4, and 24. Randomisation was stratified by baseline CD4 count (200–349 vs ≥350 cells per μL). Patients and treating physicians were not masked to treatment allocation, but the randomisation list was concealed from the investigators who assigned participants to the vaccination groups. The primary endpoint was the proportion of responders, defined as patients with hepatitis B surface antibody (anti-HBs) titres of 10 mIU/mL or more, at week 28. We did analysis by modified intention to treat. This study is registered withClinicalTrials.gov, numberNCT00670839 . Findings: Between May 19, 2008, and May 8, 2011, 178 participants were randomly assigned to the standard-dose group (n=90) or the double-dose group (n=88), of whom 176 (98%) participants were included in the primary efficacy analysis. At week 28, we recorded a response in 60 patients (67%, 95% CI 57–77) in the standard-dose group versus 64 patients (74%, 63–82) in the double-dose group (p=0·334). Except for more frequent local reactions in the double-dose group than the standard-dose group (13 [15%] vs four [4%] patients; p=0·020), there was no difference in safety between groups. Interpretation: In adults with HIV-1 who have not responded to previous hepatitis B vaccination, double-dose revaccination did not achieve a higher response rate than did revaccination with standard single-dose regimen. However, the safety profile was similar between treatment groups. Our results should be assessed in future studies before double-dose vaccine can be considered for the standard of care of vaccine non-responders. Funding: French National Institute for Medical Research–French National Agency for Research on AIDS and Viral Hepatitis.